Aggregation dynamics and magnetic properties of magnetic micrometer-sized particles dispersed in a fluid under the action of rotating magnetic fields - Llera, María Angela (2015)
We present a dynamic study of soft magnetic, commercial Fe and Ni micrometer-sized particles dispersed in oleic acid and subjected to a variable (rotating) magnetic field in the horizontal plane. A very complex structure is formed after the particles decant towards the bottom liquid?solid interface and the magnetic field is applied for several minutes. The dynamics of structure formation was studied by means of the registration and analysis of microscopic video images, through a Matlab image analysis script. Several parameters, such as the number of clusters, the perimeter-based fractal dimension and circularity, were calculated as a function of time. The time evolution of the number of clusters was found to follow a power-law behavior, with an exponent consistent with that found in other studies for magnetic systems, whereas the typical formation time depends on the particle diameter and field configuration. Complementarily, the magnetic properties of the formed structure were studied, reproducing the experiment with liquid paraffin as the containing fluid, and then letting it solidify. The sample obtained was studied by vibrating sample magnetometry. The magnetization curves show that the material obtained is a planar magnetically anisotropic material, which could eventually be used as an anisotropic magnetic sensor or actuator.